Interwencja rówieśników w sytuacji dręczenia szkolnego. Rola czynników kontekstowych. Implikacje praktyczne - Tłuściak-Deliowska, Aleksandra (Wydawnictwo Naukowe UAM, 2014)
Bullying is a group process, a social phenomenon and each group member could take on a different role. Many studies have shown that peers are present in most cases of school bullying, but behave rather in a way that perpetuates or even enhances peer violence. Prevention and intervention programs aimed at reducing school violence should take into account the role of bystanders. The point is to influence students, especially witnesses of school violence, who do nothing to stop it. The aim of this article is to: (1) indicate the main mechanisms explaining the behavior of students who witness school bullying, (2) determine, on the basis of empirical studies, the factors that may increase the likelihood of positive interventions of bullying bystanders, and (3) formulate practical implications.
Peer Intervention in Bullying Situations. The Role of Contextual Factors. Practical Implications
Keywords: bullying; bystanders; school climate; peer interventions; contextual factors